COMPARATIVE ANALYSIS OF MILITARY DOCTRINES OF INDIA AND PAKISTAN - M. S. Zaytsev (Сравнительная политика)
The article is devoted to the comparison of the military doctrines ofIndiaandPakistan; their bilateral relations greatly determine the existing balance of power in the region ofSouth Asiaand are marked with high level of tension and mutual mistrust. Since theIndependenceof the former members of the British Dominion in 1947 the sides consider each other as the main potential adversary. After nuclear tests conducted by both countries the conformation ofNew DelhiandIslamabadescalated to a new level, and the state of bilateral relations is a matter of reasonable concern all over the globe. The analysis of military doctrines ofIndiaandPakistangives every reason to think that, despite the aggressive and jingoish rhetoric of the sides, they are not ready for a full-scale war, and military warfare will be limited and short-term.